Comparison of haemodynamic effects of oral hydralazine and prazosin hydrochloride in patients with chronic congestive heart failure. Issue 6 (December 1979) - Chatterjee, K; Ports, T A; Arnold, S; Brundage, B; Parmley, W
Abstract : The comparative haemodynamic effects of oral prazosin hydrochloride and hydralazine were evaluated in 11 patients with chronic congestive heart failure. The maximum total dose of prazosin received by an individual varied up to 25 mg. Ten patients received a maximum of 75 mg and one received 50 mg of hydralazine at six-hour intervals. There was no significant change in heart rate with either drug. Decrease in mean arterial and left ventricular filling pressures were modest and similar with both agents. With prazosin, the average cardiac index increased 20 per cent and systemic vascular resistance decreased 20 per cent. By contrast, hydralazine increased cardiac index by 58 per cent and decreased systemic vascular resistance by 40 per cent. The increase in stroke work and stroke volume indices was significantly greater with hydralazine than with prazosin. These findings suggest that in some patients with severe chronic congestive heart failure, improvement in left ventricular performance may be greater with hydralazine than with prazosin.